Generalized Viscosity Approximation Methods of Ishikawa Type for Nonexpansive Mappings in Hilbert Spaces - Beheshti, M.; Azhini, M. (Armenian Journal of Mathematics, 2018)
In this paper, by using generalized viscosity mappings, we prove two strong convergence theorems for finding fixed points of a nonexpansive mapping which is also a unique solution of the variational inequality. Our results extend and improve the recent ones announced by some authors.
Keywords: Fixed point; nonexpansive mapping; contractive mapping; convergence theorem